Postnatal probiotics and allergic disease in very preterm infants: Sub‐study to the ProPrems randomized trial. Issue 1 (8th November 2019) - Plummer, Erica L.; Chebar Lozinsky, Adriana; Tobin, Jacinta M.; Uebergang, Jessica B.; Axelrad, Christine; Garland, Suzanne M.; Jacobs, Susan E.; Tang, Mimi L. K.; ,
Abstract: Background: Probiotic supplementation to mothers and/or their term‐born infants has been suggested to prevent allergic disease, in particular eczema; however, no studies have investigated probiotics for prevention of allergic diseases in very preterm infants. We evaluated the effect of a postnatal probiotic combination on development of allergic diseases in very preterm infants. Methods: This sub‐study was an a priori secondary outcome of the ProPrems multi‐center, double‐blind, placebo‐controlled randomized trial (ANZCTR:12607000144415). ProPrems randomized 1099 very preterm infants to receive a probiotic combination or placebo from soon after birth until discharge from hospital or term corrected age (CA), whichever was earlier. Allergic disease (eczema, atopic eczema, food allergy, wheeze, atopic sensitization) was assessed in a subgroup of ProPrems infants (n = 281) as close to 12 months CA as possible by questionnaire, clinical examination, and skin prick tests to common allergens. Results: There was no difference in eczema incidence between the probiotic and placebo groups (35[30%] of 118 infants vs 37[27%] of 137 infants, respectively, absolute difference 2.65%, 95% CI −8.45 to 13.75). Similarly, the incidence of atopic eczema (6[5%] of 118 vs 3[2%] of 137), food allergy (4[3%] of 124 vs 2[1%] of 154), wheeze (39[31%] of 127 vs 45[29%] of 154), and atopic sensitization (14[13%] of 106 vs 13[11%] of 123) were similar between the probiotic and placebo groups. Conclusion: This study found no effect of postnatal administration of a probiotic combination on the incidence of allergic diseases or atopic sensitization in the first 2 years of life in children born very preterm. Evidence that probiotics are effective for prevention of allergic disease in premature infants remains lacking; adequately powered randomized controlled trials evaluating probiotic supplementation for allergy prevention in very preterm infants are needed. Abstract : We evaluated the effect of postnatal probiotic supplementation on the development of allergic diseases and atopic sensitization in very preterm infants. We found no difference in the incidence of allergic diseases or atopic sensitization between the probiotic and placebo groups. Although current guidelines recommend probiotics for prevention of allergic diseases in high‐risk infants, our findings demonstrate that there is insufficient evidence to determine whether the guideline recommendations are applicable to very preterm infants.